ROS 2018
DOI: 10.20455/ros.2018.809
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Fluorescence-Based Assay for the Measurement of Biliverdin Reductase Activity

Abstract: Biliverdin reductase (BVR) is the enzyme responsible for the last step in the production of bilirubin from the breakdown of heme. Bilirubin is one of the most potent antioxidant molecules in the body. Monitoring BVR activity is essential in studying the antioxidant capacity of cells and tissues. Traditional methods of determining BVR activity have relied on the measurement of bilirubin converted from biliverdin using absorbance spectroscopy. The approach has limited sensitivity and requires large quantities of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 17 publications
0
20
0
4
Order By: Relevance
“…Bilirubin has strong antioxidant properties, and we have shown that it also signals through the nuclear hormone receptor PPARα to up-regulate genes associated with increased fatty acid oxidation and glucose sensitization [72,73]. Bilividen is rapidly converted to bilirubin by BVRA [74], and biliverdin treatment in diabetic [75] or obese [76] mice improves metabolic dysfunction. However, biliverdin treatment in human HepG2 hepatocytes with PPARα knockdown attenuates transcriptome responses [73].…”
Section: Discussionmentioning
confidence: 93%
“…Bilirubin has strong antioxidant properties, and we have shown that it also signals through the nuclear hormone receptor PPARα to up-regulate genes associated with increased fatty acid oxidation and glucose sensitization [72,73]. Bilividen is rapidly converted to bilirubin by BVRA [74], and biliverdin treatment in diabetic [75] or obese [76] mice improves metabolic dysfunction. However, biliverdin treatment in human HepG2 hepatocytes with PPARα knockdown attenuates transcriptome responses [73].…”
Section: Discussionmentioning
confidence: 93%
“…We had previously shown that mice with the Gilbert's mutation UGT1A1*28 and hyperbilirubinemia were resistant to high-fat diet-induced hepatic steatosis by inhibiting de novo lipogenesis and activation of β-oxidation (Hinds et al, 2017). We have also shown that exercise elevated plasma bilirubin by suppressing hepatic UGT1A1 and increasing biliverdin reductase-A (BVRA) (Hinds et al, 2020), the enzyme that generates bilirubin (Adeosun et al, 2018;O'Brien et al, 2015), which improved hepatic glycogen storage and PPARα target genes (Hinds et al, 2020). Here, we found that PEG-BR reduced SCD1 and FAS while activating PPARα and ACOX1, improving hepatic steatosis in obese mice.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there has been a correlation showing that plasma bilirubin levels are lower in obese humans [3][4][5]. The enzyme that produces bilirubin, BVRA [6,7], is also reduced in obese humans compared to lean matched controls [8]. Studies indicate that bilirubin levels might increase with exercise [9,10] and fasting [11][12][13][14], implying a possible role for metabolic regulation.…”
Section: Introductionmentioning
confidence: 99%